Assessment of heavy metal contamination in bottom sediments due to long-term exposure to TPP - Rychak , T. L. (Man and Environment. Issues of Neoecology, 2026)
Purposes. To assess the geochemical and ecological status of bottom sediments within the “Gnyla Lypa River – Burshtyn Reservoir – Dniester River” hydrological system.Methods. Field and analytical methods, with a systematic approach to synthesizing the results.Results. Sediment samples were collected at seven representative sites within the hydrological system. To interpret data on heavy metal content (Cu, Zn, Cd, Pb), the following indicators were used: geoaccumulation index, enrichment factor, pollution index, and toxicological screening. The obtained geoaccumulation index values indicate ecological well-being, and the geochemical cycle of Zn in the Gnyla Lypa River basin is determined exclusively by natural lithogenic processes. The calculated enrichment factor values for Cd at the third section indicate an anthropogenic component. It has been established that the pollution index values at sections No. 3 and No. 5 indicate a state of anthropogenic degradation; at the background and terminal sections, the index indicates the absence of pollution. The highest toxicological screening was detected for Cd at section No. 3, which provides grounds for asserting the presence of a latent ecological load that, under unfavorable hydrochemical conditions, could transform into a real threat to benthic biocenoses. The calculated values of total toxicity vary within ranges corresponding to low and moderate levels of ecotoxicological risk. The highest value of the coefficient was recorded in the accumulation zone (station No. 3), indicating an increase in biological risk due to the synergistic effect of accumulated heavy metals. The values of the pollution load index and the pollution index indicated that the environmental risk associated with the presence of heavy metals in the bottom sediments of rivers and reservoirs was moderate.Conclusions. The results of the study are of practical significance for the development of environmental management strategies for the Hnyla Lypa–Dniester river system. The measured levels of heavy metal accumulation in bottom sediments serve as a basis for assessing the ecotoxicological status of the reservoir and predicting the resilience of aquatic ecosystems to anthropogenic impacts.